Accuracy of screening tests for gestational diabetes mellitus in Southeast Asia: A systematic review of diagnostic test accuracy studies. Issue 46 (13th November 2020) - Lappharat, Sattamat; Liabsuetrakul, Tippawan
Abstract: Background: To investigate the accuracy of screening tests for gestational diabetes mellitus (GDM) in Southeast Asian pregnant women. Methods: We searched PubMed (MEDLINE), Web of Science, Cochrane Library, ClinicalTrials.gov, Google Scholar, and Google for relevant articles published in English up to November 2018 using search terms related to GDM, screening tests for GDM and diagnostic performance. The studies were independently screened and selected by both authors. The methodological quality of the included studies was independently assessed by quality assessment of diagnostic accuracy studies 2. A hierarchical summary receiver operating characteristic (HSROC) model was created to estimate the HSROC curve. The summary sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio were calculated in a meta-analysis using bivariate random-effects model. Results: A total of 19 studies were included in which the 100 g oral glucose tolerance test (OGTT) and 75 g OGTT were the two common reference standards for diagnosis of GDM. Most points of diagnostic performance in the HSROC 50 g GCT curve compared with the 100 g OGTT reference standard were clustered in the upper left-hand quadrant. The pooled sensitivity and specificity of the 50 g GCT were 79% (95% confidence interval [CI] 64%–89%) and 74% (95% CI 59%–85%), respectively. For the 75 g OGTT reference standard, the non-fasting 2-hour plasma glucose showed quite similar sensitivity the 50 g GCT compared with the 100 g OGTT reference standard. The pooled sensitivities and specificities of the fasting plasma glucose and hemoglobin A1c were 81% (95% CI 76%–86%) and 70% (95% CI 67%–72%), and 80% (95% CI 66%–90%) and 69% (95% CI 58%–78%), respectively. Conclusion: Our findings indicate that the 50 g GCT using the threshold of 140 mg/dL is a good screening test for identifying GDM at 24 to 28 weeks' gestational age for both high-risk and universal screening strategies in Southeast Asian countries. The non-fasting 2-hour PG, fasting plasma glucose or hemoglobin A1c are alternative choices for screening. Abstract : Supplemental Digital Content is available in the text